The Heidelberg appendicitis score simplifies identification of pediatric appendicitis - Boettcher, Michael; Breil, Thomas; Günther, Patrick (Indian journal of pediatrics, 2016)
ObjectiveTo identify the factors that facilitate the diagnosis of pediatric appendicitis.MethodsInstitutionally approved retrospective, single center analysis of all patients with acute abdominal pain was done. Medical history, symptoms, laboratory and radiologic findings of all children presenting with abdominal pain were evaluated. To identify the best predictors, uni- and multi-variate analysis were used.ResultsIn 2 years, 431 patients fulfilled the inclusion criteria. Data was complete in all subjects. Of these, 156 (36.2 %) suffered from appendicitis. The best discriminators for appendicitis were clinical and ultrasound features. The four best factors were identified by CART analysis (continuous abdominal pain, tenderness on the right lower quadrant, rebound tenderness and conspicuous ultrasound) and combined to the Heidelberg Appendicitis score. A positive score (>3 features) is highly predictive for acute appendicitis (PPV 89.3 %, NPV 94.9 %) and includes all cases of perforated appendicitis.ConclusionsIt is possible to predict acute appendicitis in children. The decision making process can be simplified by the proposed Heidelberg Appendicitis score, which is comprised of four factors. It has great potential to facilitate and accelerate the diagnosis of pediatric appendicitis.